Composite green pickling material and use method thereof
By using composite green pickling materials, the combination of organic sulfonic acid and phosphoric acid is used to control the pickling speed, and citric acid is used to stabilize free iron ions, which solves the problems of large acid mist volatilization and excessive corrosion of the substrate in the existing pickling process. Efficient, uniform pickling effects and long-life pickling materials are achieved.
Patent Information
- Application Number
- CN202411947404.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-12-27
AI Technical Summary
The existing pickling process has problems such as large volatility of acid mist, over-corrosion of substrates, and difficulty in regeneration of waste acids. The pickling speed is uneven, making it difficult to meet the pickling efficiency requirements of bulk substrates.
The material is made of composite green pickling material. This material consists of organic sulfonic acid, phosphate, pickling promotent and water. It is slowly released by the ternary acid buffer structure of phosphate, controlled the possibility of the pickle, and stabilized through the addition of citric acid. Free iron ion concentration, improve the picking speed and efficiency.
It realizes the fast and uniform possibility, reduces the corrosion of the substrate, prolongs the service life of the pickling material, and has a small impact on the corrosion of the environment and green and environmentally friendly.
Abstract
Description
Technical Field
[0001] The invention discloses a composite green pickling material and a use method thereof, belonging to the technical field of pickling materials. Background Art
[0002] Before the hot-rolled substrate is processed downstream, the surface iron oxide scale needs to be removed, also known as descaling. Currently, the descaling of hot-rolled substrates is almost always done by pickling with strong acids such as hydrochloric acid. Due to the inherent physical and chemical properties of hydrochloric acid, there are inevitably environmental and process problems such as large acid mist volatilization, severe over-corrosion of the substrate, and difficulty in regenerating waste acid during the pickling and descaling process. In view of this, scientific and technological workers have been conducting research on green alternative processes for hydrochloric acid pickling, mainly physical and chemical methods.
[0003] The physical method, i.e. the mechanical descaling process, does not completely remove phosphorus and cannot meet the surface cleanliness requirements of subsequent treatment processes. The new chemical dephosphorization process has the limitation that the pickling speed is significantly slower than the traditional hydrochloric acid pickling process.
[0004] In addition, it is difficult to achieve multiple reuse of existing pickling composition materials. After one pickling, hydrogen ions will be completely released. On the one hand, a small amount of pickling liquid for cleaning substrates will be seriously wasted, which is not conducive to environmental protection. On the other hand, the pickling speed is difficult to control and the speed is uneven. A large amount of hydrogen ions will fully play the pickling effect in a short time, which will cause serious corrosion of the substrate, or uneven pickling of the substrate surface, and low pickling quality. For some pickling composition materials that can be reused, weak acids other than hydrochloric acid, nitric acid or hydrofluoric acid are generally used. In addition to the pickling speed that is still uncontrollable and uneven, the pickling speed of these pickling composition materials is relatively low, which is difficult to meet the pickling efficiency requirements of bulk substrates. Summary of the invention
[0005] The technical problem to be solved by the present invention is to overcome the shortcomings of the prior art and provide a composite green pickling material and a method for using the same, which has a fast pickling speed, uniform speed in each pickling stage, low environmental corrosion impact, is green and environmentally friendly, and has a long service life.
[0006] The technical solution adopted by the present invention to solve the technical problem is: a composite green pickling material, characterized in that the raw materials include 5-15 wt% of organic sulfonic acid, 3-8 wt% of phosphoric acid, 1.9-9.6 wt% of pickling accelerator and the balance of water.
[0007] Organic sulfonic acid can provide a large amount of free hydrogen ions, while phosphoric acid utilizes its special ternary acid buffer structure, and phosphate slowly releases free hydrogen ions to buffer the excessive free hydrogen ion concentration in the pickling material, which can control and stabilize the pickling speed of the pickling solution, which is not only conducive to controlling the pickling degree, but also can protect the substrate metal and avoid corrosion of the substrate. In addition, phosphate slowly releases and buffers and controls free hydrogen ions, and the free hydrogen ion concentration is more stable, the pickling effect decreases less, and the service life of the pickling material is greatly extended, and it can be used repeatedly for a long time. Under the cooperation of organic sulfonic acid and phosphoric acid, free hydrogen ions can be more evenly dispersed, and substrate corrosion caused by hydrogen ion accumulation in the exposed area of the substrate can be avoided, and the substrate can be further protected. Moreover, phosphoric acid itself can also release hydrogen ions, and cooperates with the organic sulfonic acid with the weight content to synergistically enhance the effect, which can significantly improve the pickling speed and pickling efficiency, reach the same pickling speed as that of inorganic strong acid, and avoid corrosion of the substrate due to excessive concentration. Moreover, the composite green pickling material does not contain volatile strong acid, has little corrosion to the environment, and is green and environmentally friendly.
[0008] Preferably, 1-5 wt % of citric acid is also included.
[0009] Citric acid can release free citrate radicals in the pickling material. The free citrate radicals have a chelating effect on iron ions, which can enrich and flocculate the free iron ions after pickling, reduce the concentration of free iron ions in the pickling material, thereby maintaining the pickling ability of the pickling material, and further stabilizing and improving the pickling speed. Moreover, as a strong organic acid, citric acid can also produce complementary synergy with phosphoric acid to improve the pickling ability and pickling speed.
[0010] Further preferably, the raw materials include 10 wt % of organic sulfonic acid, 3 wt % of citric acid, 5 wt % of phosphoric acid, 1.9-9.6 wt % of a pickling accelerator, and the balance water.
[0011] With the optimal composition and concentration, the pickling material has the strongest pickling ability and a higher pickling speed, while also ensuring the protective effect on the substrate.
[0012] Preferably, the organic sulfonic acid comprises one or a mixture of any proportion of methanesulfonic acid, aminosulfonic acid and β-naphthalenesulfonic acid.
[0013] The preferred organic sulfonic acid has a better coordination effect with phosphoric acid, has a stronger pickling effect, and has a faster and more stable pickling speed.
[0014] Preferably, the pickling accelerator comprises 0.2-1.0 wt% of an activator, 1-5 wt% of a reducing agent, 0.5-3 wt% of a surfactant and 0.2-0.6 wt% of a corrosion inhibitor.
[0015] Preferably, the pickling accelerator can appropriately increase the acidity, improve the pickling speed, reduce the pickling temperature, and inhibit corrosion and protect the substrate.
[0016] Further preferably, the activator comprises one or a mixture of any proportion of chloride salts, fluoride salts and nitrate salts.
[0017] The preferred activator can improve the pickling ability of the pickling material: chloride salts, fluoride salts and nitrates can release Cl in the pickling material. - 、F - or NO3 - These anions combine with free hydrogen ions in the pickling material to form a small amount of inorganic strong acid, which makes the pickling material have stronger local descaling activity. For example, it can effectively strip off the difficult-to-treat iron oxide scale and high-priced iron oxide (inert points) on the surface of the substrate, and the pickling effect is better and faster. It supplements the extreme descaling ability of organic sulfonic acid and phosphoric acid, improves the pickling effect, and also reduces the acid consumption, further extending the service life of the pickling material.
[0018] Further preferably, the reducing agent comprises one or a mixture of any proportion of potassium sulfite, stannous chloride, potassium bisulfite, potassium hyposulfite and ascorbic acid.
[0019] The activator strong acid anion directly strips the inert point oxide scale and has no reducing ability. The preferred reducing agent is to reduce the high-valent iron oxide to the easily reactive low-valent iron oxide to increase the reaction rate.
[0020] Further preferably, the surfactant includes one or a mixture of any proportion of sodium dodecylbenzene sulfonate (AAS), sodium fatty alcohol polyoxyethylene ether sulfate (AES), fatty alcohol polyoxyethylene ether AEO-9, alkylphenol polyoxyethylene ether (OP-10 or JFC) and coconut oil amide 6501.
[0021] The preferred surfactants have excellent wetting and penetration properties, which can improve the wetting and penetration of the pickling solution on the substrate and promote the pickling process.
[0022] Further preferably, the corrosion inhibitor comprises 0.1-0.3 wt% of corrosion inhibitor I and 0.1-0.3 wt% of corrosion inhibitor II; The corrosion inhibitor I comprises one or a mixture of any proportion of hexamethylenetetramine, morpholine, thiourea and piperazine.
[0023] The corrosion inhibitor II comprises one or a mixture of any proportion of pyridine, nonionic imidazoline and imidazoline quaternary ammonium salt.
[0024] Preferably, a two-component corrosion inhibitor is used, which can effectively protect the exposed surface of the substrate and reduce corrosion of the substrate.
[0025] The present invention also relates to a method for using the composite green pickling material, which is characterized in that the object to be cleaned is immersed in the composite green pickling material at 60-80° C. for 3-7 minutes.
[0026] When pickling in the composite green pickling material, a good pickling effect can be achieved by only using 60-80°C, and the pickling time is 3-7 minutes, which can achieve sufficient pickling of the surface oxide layer such as iron oxide scale, and at the same time can avoid excessive corrosion of the substrate.
[0027] Compared with the prior art, the present invention has the following beneficial effects: as a pickling material that does not contain volatile strong acid, it has a pickling speed and pickling effect close to those of volatile strong acid, and the pickling speed is more stable, it is easier to control the pickling degree, it is less corrosive to the substrate, and the protective effect is better; it is non-volatile, and the impact of environmental corrosion is almost negligible; it has a longer service life, can be repeatedly used for a longer period of time, fully utilizes free hydrogen ions, saves acid, and is green and environmentally friendly. DETAILED DESCRIPTION
[0028] The present invention will be further described below in conjunction with the embodiments, and Embodiment 1 is the best embodiment of the present invention.
[0029] The pickled hot-rolled substrates in the following examples and comparative examples are obtained by cutting from the same section of hot-rolled plain carbon steel and have the same oxidation degree, with the side surfaces of the substrates being completely covered with metal oxides.
[0030] Example 1 A composite green pickling material comprises raw materials including 10 wt% of methanesulfonic acid, 3 wt% of citric acid, 5 wt% of phosphoric acid, 0.6 wt% of sodium chloride, 3 wt% of potassium sulfite, 2 wt% of sodium polyoxyethylene fatty alcohol ether sulfate (AES), 0.2 wt% of hexamethylenetetramine, 0.2 wt% of imidazoline quaternary ammonium salt corrosion inhibitor and the balance of water.
[0031] The preparation method is to dissolve the solid first and then add the liquid. Specifically follow the steps below: (1) Add citric acid and activator (sodium chloride) into water according to the raw material ratio, stir and dissolve until clear, and obtain solution A; (2) Add reducing agent (potassium sulfite) and corrosion inhibitor I (hexamethylenetetramine) to solution A in sequence, stir and dissolve until clear, and obtain solution B; (3) Slowly add organic sulfonic acid (methanesulfonic acid) and phosphoric acid to solution B in sequence while stirring until the solution becomes clear, thereby obtaining solution C; (4) Slowly add surfactant (sodium fatty alcohol polyoxyethylene ether sulfate (AES)) and corrosion inhibitor II (imidazoline quaternary ammonium salt corrosion inhibitor) to solution C while stirring, and add a small amount of defoaming agent until the solution is clarified, and then the composite green pickling material can be obtained.
[0032] A method for using a composite green pickling material comprises immersing a hot-rolled substrate with an oxidized surface into the obtained composite green pickling composition, wherein the temperature of the composite green pickling composition is 70°C.
[0033] The pickling is completed when no black-gray metal oxide remains on the surface of the substrate. The pickling time is 3 minutes.
[0034] Example 2 A composite green pickling material comprises raw materials including 13 wt% of methanesulfonic acid, 5 wt% of phosphoric acid, 0.6 wt% of sodium chloride, 3 wt% of potassium sulfite, 2 wt% of sodium polyoxyethylene fatty alcohol ether sulfate (AES), 0.2 wt% of hexamethylenetetramine, 0.2 wt% of imidazoline quaternary ammonium salt corrosion inhibitor and the balance of water.
[0035] The other conditions were the same as those in Example 1, the method of use was the same as that in Example 1, and the final pickling time was 5 minutes.
[0036] Example 3 A composite green pickling material comprises raw materials including 13 wt% of beta-naphthalenesulfonic acid, 1 wt% of citric acid, 5 wt% of phosphoric acid, 0.6 wt% of sodium chloride, 3 wt% of potassium sulfite, 2 wt% of sodium polyoxyethylene fatty alcohol ether sulfate (AES), 0.2 wt% of hexamethylenetetramine, 0.2 wt% of imidazoline quaternary ammonium salt corrosion inhibitor and the balance of water.
[0037] The other conditions were the same as those in Example 1, the method of use was the same as that in Example 1, and the final pickling time was 4 minutes.
[0038] Example 4 A composite green pickling material comprises raw materials including 10 wt% of methanesulfonic acid, 3 wt% of citric acid, 8 wt% of phosphoric acid, 0.6 wt% of sodium chloride, 3 wt% of potassium sulfite, 2 wt% of sodium polyoxyethylene fatty alcohol ether sulfate (AES), 0.2 wt% of hexamethylenetetramine, 0.2 wt% of imidazoline quaternary ammonium salt corrosion inhibitor and the balance of water.
[0039] The other conditions were the same as those in Example 1, the method of use was the same as that in Example 1, and the final pickling time was 3 minutes.
[0040] Example 5 A composite green pickling material, based on Example 1, wherein sodium chloride is replaced by sodium fluoride, and other conditions are the same as those of Example 1.
[0041] The method of use is the same as in Example 1, and the final pickling time is 3 minutes.
[0042] Example 6 A composite green pickling material, based on Example 1, potassium sulfite is replaced by 5 wt % ascorbic acid, and other conditions are the same as those in Example 1.
[0043] The method of use is the same as in Example 1, and the final pickling time is 4 minutes.
[0044] Example 7 A composite green pickling material, based on Example 1, wherein fatty alcohol polyoxyethylene ether sodium sulfate (AES) is replaced by fatty alcohol polyoxyethylene ether AEO-9, and other conditions are the same as those in Example 1.
[0045] The method of use is the same as in Example 1, and the final pickling time is 4 minutes.
[0046] Example 8 A composite green pickling material, based on Example 1, the corrosion inhibitor hexamethylenetetramine 0.2 wt% and the imidazoline quaternary ammonium salt corrosion inhibitor 0.2 wt% are replaced by only morpholine 0.6 wt%, and other conditions are the same as in Example 1.
[0047] The method of use is the same as in Example 1, and the final pickling time is 4 minutes.
[0048] Comparative Example 1 A pickling material is a 13wt% hydrochloric acid solution.
[0049] After the pickling solution is prepared, it is heated to 80°C to soak the hot-rolled substrate with surface oxidation. The pickling is considered complete when no black-gray metal oxide remains on the surface of the substrate. The pickling time is 3 minutes.
[0050] Comparative Example 2 A pickling material comprises 17 wt% of methanesulfonic acid, 0.6 wt% of sodium chloride, 3 wt% of potassium sulfite, 2 wt% of sodium polyoxyethylene fatty alcohol ether sulfate (AES), 0.2 wt% of hexamethylenetetramine, 0.2 wt% of imidazoline quaternary ammonium salt corrosion inhibitor and the balance of water.
[0051] The method of use is the same as in Example 1, and the final pickling time is 6 minutes.
[0052] Comparative Example 3 A pickling material comprises 10 wt% of citric acid, 8 wt% of phosphoric acid, 0.6 wt% of sodium chloride, 3 wt% of potassium sulfite, 2 wt% of sodium polyoxyethylene fatty alcohol ether sulfate (AES), 0.2 wt% of hexamethylenetetramine, 0.2 wt% of imidazoline quaternary ammonium salt corrosion inhibitor and the balance of water.
[0053] The method of use is the same as in Example 1, and the final pickling time is 10 minutes.
[0054] Comparative Example 4 A pickling material comprises 18 wt% of methanesulfonic acid, 3 wt% of citric acid, 5 wt% of phosphoric acid, 0.6 wt% of sodium chloride, 3 wt% of potassium sulfite, 2 wt% of sodium polyoxyethylene fatty alcohol ether sulfate (AES), 0.2 wt% of hexamethylenetetramine, 0.2 wt% of imidazoline quaternary ammonium salt corrosion inhibitor and the balance of water.
[0055] The method of use is the same as in Example 1, and the final pickling time is 3 minutes.
[0056] Comparative Example 5 A pickling material comprises 18 wt% of methanesulfonic acid, 3 wt% of citric acid, 8 wt% of phosphoric acid, 0.6 wt% of sodium chloride, 3 wt% of potassium sulfite, 2 wt% of sodium polyoxyethylene fatty alcohol ether sulfate (AES), 0.2 wt% of hexamethylenetetramine, 0.2 wt% of imidazoline quaternary ammonium salt corrosion inhibitor and the balance of water.
[0057] The method of use is the same as in Example 1, and the final pickling time is 2 minutes.
[0058] Performance Testing In addition to the performance test of the pickling speed (time) of the above embodiments and comparative examples, the weight loss rate, acid consumption rate and life of the substrate of each embodiment and comparative example were also tested.
[0059] Substrate weight loss rate: the percentage of substrate weight reduction before and after the oxide scale is completely removed. The calculation formula is: .
[0060] The weight loss rate of the substrate indicates the extent of acid corrosion of the substrate. When there is no ferrous metal oxide remaining on the surface of the substrate after pickling, the smaller the weight loss rate of the substrate, the less corrosion the substrate suffers.
[0061] Acid consumption rate: The free acid consumed to remove the oxide scale per unit area when the pickling material is used for the first time, and is tested by free acid chemical titration. The acid consumption rate can reflect the efficiency of pickling. The smaller the acid consumption rate, the higher the pickling efficiency.
[0062] Life test: After the pickling material obtained in each embodiment and comparative example is pickled once, the same volume of pickling material is used to pickle the substrate with the same oxidation degree until it is qualified, and then it is reused until Fe 2+ and Fe 3+ Content of 110 g / L or above, Fe 2+ and Fe 3+The concentration is tested by iron ion chemical titration method, and the total number of times the pickling material has been used for pickling is recorded as the test result.
[0063] The final test results are shown in Table 1 below.
[0064] Table 1 Test results .
[0065] According to the comparison results of Example 1 and Comparative Example 1, the composite green pickling material of the present invention can reach the pickling speed of the hydrochloric acid type pickling material, and has a smaller substrate corrosion degree, acid consumption rate and service life (higher pickling efficiency). At the same time, the corrosion degree can prove that the overall pickling degree of the composite green pickling material obtained in Example 1 is more uniform, more inclined to metal oxides, and has a better protection effect on the substrate. And Example 1 and Comparative Examples 2 and 3 can prove that phosphoric acid and organic sulfonic acid have a certain special synergistic effect, and the free hydrogen release effect of phosphoric acid buffering organic sulfonic acid can not only appropriately increase the acidity to increase the pickling speed and greatly reduce the acid consumption rate, but also fully retain the organic acid's own characteristics to reduce the corrosion effect on the substrate. The comparison results of Example 1 and Comparative Examples 4 and 5 can prove that simply increasing the acid content in the pickling material cannot increase the pickling speed, but will cause the buffering synergistic system of organic sulfonic acid and phosphoric acid to collapse, and the acid consumption rate will rise rapidly, thereby causing excessive corrosion of the substrate.
[0066] By comparing the results of Example 2 with Example 1, it can be seen that the addition of citric acid can maintain the free iron ion concentration during the pickling process, and then cooperate with the ternary acid buffer structure of phosphoric acid to stabilize the free hydrogen ion concentration in the pickling material, making the free hydrogen ion concentration of the entire pickling process more stable, ensuring the pickling speed, and extending the service life.
[0067] The above is only a preferred embodiment of the present invention, and does not limit the present invention in other forms. Any technician familiar with the profession may use the above disclosed technical content to change or modify it into an equivalent embodiment with equivalent changes. However, any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the technical solution of the present invention still belongs to the protection scope of the technical solution of the present invention.
Claims
1. A composite green pickling material, characterized in that: The raw materials include 5-15 wt% of organic sulfonic acid, 3-8 wt% of phosphoric acid, 1.9-9.6 wt% of pickling accelerator and the balance of water.
2. The composite green pickling material according to claim 1, characterized in that: The raw materials also include 1-5 wt% of citric acid.
3. The composite green pickling material according to claim 2, characterized in that: The raw materials include 10 wt% of organic sulfonic acid, 3 wt% of citric acid, 5 wt% of phosphoric acid, 1.9-9.6 wt% of a pickling accelerator and the balance of water.
4. The composite green pickling material according to claim 1, characterized in that: The organic sulfonic acid includes one or a mixture of any proportion of methanesulfonic acid, aminosulfonic acid and beta-naphthalenesulfonic acid.
5. The composite green pickling material according to claim 1, characterized in that: The pickling accelerator comprises 0.2-1.0 wt% of an activator, 1-5 wt% of a reducing agent, 0.5-3 wt% of a surfactant and 0.2-0.6 wt% of a corrosion inhibitor.
6. The composite green pickling material according to claim 5, characterized in that: The activator comprises one or a mixture of any proportion of chloride salt, fluoride salt and nitrate salt.
7. The composite green pickling material according to claim 5, characterized in that: The reducing agent comprises one or a mixture of any proportion of potassium sulfite, stannous chloride, potassium hydrogen sulfite, potassium hyposulfite and ascorbic acid.
8. The composite green pickling material according to claim 5, characterized in that: The surfactant comprises one or a mixture of any proportion of sodium dodecylbenzene sulfonate, sodium fatty alcohol polyoxyethylene ether sulfate, fatty alcohol polyoxyethylene ether AEO-9, alkylphenol polyoxyethylene ether and coconut oil amide 6501.
9. The composite green pickling material according to claim 5, characterized in that: The corrosion inhibitor comprises 0.1-0.3 wt% of corrosion inhibitor I and 0.1-0.3 wt% of corrosion inhibitor II; The corrosion inhibitor I comprises one or a mixture of any proportion of hexamethylenetetramine, morpholine, thiourea and piperazine; The corrosion inhibitor II comprises one or a mixture of any proportion of pyridine, nonionic imidazoline and imidazoline quaternary ammonium salt.
10. A method for using the composite green pickling material according to any one of claims 1 to 9, characterized in that: The object to be cleaned is immersed in the composite green pickling material at 60-80° C. for 3-7 minutes.
Citation Information
Patent Citations
Silicon steel acid cleaning stabilizing material and application method thereof
CN103103541A
Corrosion-inhibiting mist-suppressing promoter for steel pickling
CN103205765A
Room temperature low damage pickling solution of 300 series stainless steel tubes and pickling method thereof
CN105780025A
Composition used for corrosion inhibitor and application thereof and method for pickling equipment
CN105821422A
Efficient environment-friendly rust remover as well as preparation method and application thereof
CN112795928A